Sejarah Pembangunan Dan Reformasi Ekonomi China - Setiawan, Zudi (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2025)
China has succeeded as a driver of the world economy, and is now one of the world's economic giants. What China has achieved is the result of hard work and intelligence of Chinese leaders, business people and the Chinese people. Rapid growth occurred especially after the implementation of China's economic reform policy in 1979. The purpose of this study is to find out the history of China's economic development and reform. This research is a qualitative study using literature studies. The theory used in this study is Kuntowijoyo's theory related to five stages in historical research, including topic selection, source collection, verification of historical criticism, interpretation, and writing. The data analysis of this study uses a qualitative approach. Based on the results of this study, it can be explained that China has a very long history, especially in the economic sector. Its monetary power in the global sector is felt by many countries in the world. Since the economic reform in 1979, the poverty rate of the Chinese population has fallen from 53% in 1981 to 1.7% in 2018. Over the past few years, China has become the most progressive and largest economy in the world. Keywords : China, History, Reform, Economy, Development ABSTRAK China berhasil sebagai penggerak ekonomi dunia, dan kini menjadi salah satu raksasa ekonomi dunia. Apa yang dicapai oleh China merupakan hasil kerja keras, dan cerdas para pemimpin China, para pelaku bisnis dan rakyat China. Pertumbuhan pesat terjadi terutama setelah diterapkannya kebijakan reformasi ekonomi China pada 1979. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana sejarah pembangunan dan reformasi ekonomi China. Penelitian ini adalah penelitian kualitatif dengan menggunakan studi pustaka. Teori yang digunakan dalam penelitian ini yaitu teorinya Kuntowijoyo terkait dengan lima tahapan dalam penelitian sejarah, di antaranya adalah pemilihan topik, pengumpulan sumber, verifikasi kritik sejarah, interpretasi, dan penulisan. Analisis data penelitian ini menggunakan pendekatan kualitatif. Berdasarkan hasil penelitian ini dapat dijelaskan bahwa China memiliki sejarah yang sangat panjang, khususnya di bidang ekonomi. Kekuatan moneternya di bidang global dirasakan oleh banyak negara di dunia. Sejak reformasi ekonomi pada 1979, laju kemiskinan populasi China telah turun dari 53% pada tahun 1981 menjadi 1,7% pada tahun 2018. Selama beberapa tahun terakhir, China telah menjadi negara dengan ekonomi paling progresif dan terbesar di dunia. Kata Kunci : China, Sejarah, Reformasi, Ekonomi, Pembangunan